Multidetector CT Angiography in Diagnosing Type I and Type IVA Spinal Vascular Malformations - Lai, P.H.; Weng, M.J.; Lee, K.W.; Pan, H.B. (American Journal of Neuroradiology, 2006)
SUMMARY: Multidetector CT (MDCT) angiography is an imaging technique that can provide high-resolution and high-contrast images; however, published reports of MDCT angiography in the evaluation of spinal vascular malformations are limited. We present 2 cases in which MDCT angiography led to diagnosis of a type I (spinal dural arteriovenous fistula) in one and type IVA (perimedullary spinal cord simple arteriovenous fistula fed by a single arterial feeder) spinal vascular malformation, both confirmed by conventional angiography. MDCT angiography can localize the feeding vessel and the fistula, thus greatly reducing the amount of time required for conventional angiography.